Menelaah Model Gabungan Kepemimpinan dan Kekuasaan dalam Mempengaruhi Hasil Organisasi - Komala Maharani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to explore a combined model of leadership and power in the context of influencing organizational outcomes. The focus of this study is on the relationship between leadership style, influence tactics, and distribution of power and the achievement of organizational goals. Through an analytical approach, this study evaluates various possible integration models between these three factors, as well as their impact on organizational effectiveness. In-depth analysis is conducted to highlight the ways in which the combination of leadership and power can shape internal dynamics that influence overall organizational outcomes.